REKONDISI MESIN-MESIN TTG GUNA MENINGKATKAN KAPASITAS PRODUKSI ANEKA KRIPIK DI UMKM “TIA MELATI” KABUPATEN LUWU TIMUR, SULAWESI SELATAN - Harman, Harman (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Micro business called UMKM is currently considered an effective means of alleviating poverty because it can create sizable job opportunities for domestic workers, thus greatly assisting the government in reducing unemployment. This has become the concern of the government in several regions. The local government has disbursed several budgets to provide Appropriate Technology (TTG) machines for UMKM actors. However, UMKM actors face many obstacles when they receive machine assistance from the government. The unpreparedness of human resources causes technology transfer not to work. It is not uncommon for beneficiaries to have only junior high school to elementary school education. Meanwhile, TTG machines are prone to damage if they are not cared for properly, so many machines end up badly damaged, and their owners cannot repair them. UMKMs, as the chosen activity partner, are TIA MELATI. This selection is based on visits to Partner locations, and information is obtained that the Partner's production decline is due to the damaged TTG machines that are owned but need the ability to make improvements both in terms of knowledge and from a cost standpoint. This activity aims to assist UMKM players in East Luwu to increase production capacity and expand the reach of product marketing to increase production, which impacts the welfare of its members. The results are that TTG machines owned by partners can function again so that production increases, as well as increased knowledge and ability to maintain and repair TTG machines owned.